Effect of printing parameters on sintered WC-Co components by binder jetting. Issue 1 (31st December 2022) - Mariani, Marco; Mariani, Davide; De Gaudenzi, Gian Pietro; Lecis, Nora
Abstract: Hardmetals are materials employed to produce cutting and forming tools as well as wear resistant parts. Standard powder metallurgy suffers limitations in the manufacturing of shapes required by application-oriented design. Therefore, there is interest for the implementation of additive manufacturing, in particular low temperature techniques as binder jetting because they allow to preserve microstructures and peculiar properties. In our work, the powder was tungsten carbide with 12 wt.% cobalt (WC-Co). Shaping by binder jetting was followed by curing treatment to promote the binder polymerization, vacuum sintering and sinter-HIP to achieve near-full density. The powder was analysed in terms of size and shape, to determine its suitability for the procedure. Then, the effects of different combinations of printing parameters, layer thickness (50–100 μm) and binder saturation (60/75/90%), on the density of the green bodies were analysed. Finally, the relative density of the sintered components was measured and the pores shape and size were studied by SEM imaging, to assess possible consequences of the deposition procedure. Vickers hardness along the samples cross-section was measured and correlated to the printing conditions employed.